2021
DOI: 10.1186/s12884-021-03594-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of thyroid antibodies status on the outcomes of pregnant women with hypothyroidism (maternal hypothyroidism on pregnancy outcomes, MHPO-4)

Abstract: Background Autoimmunity increases with age and is often commonly evaluated in women of the reproductive age group. Prevalence of thyroid antibodies is common even in euthyroid pregnant women. We aim to compare the association of thyroid antibody status on the maternal and neonatal outcomes in pregnant women with hypothyroidism. Methods We conducted a cross-sectional retrospective study on 718 cases in the Aga Khan University Hospital. Information w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…In another study, IUFD was noted in 2.4% of women with thyroid peroxidase antibodies and 3.1% of women with thyroglobulin antibodies. In women without thyroid antibodies, none of them had any fetal loss [ 35 ]. In a study by Meena et al, no difference was noted in IUFD in both groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, IUFD was noted in 2.4% of women with thyroid peroxidase antibodies and 3.1% of women with thyroglobulin antibodies. In women without thyroid antibodies, none of them had any fetal loss [ 35 ]. In a study by Meena et al, no difference was noted in IUFD in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, no association was noted [ 33 ] and some authors have reported prolonged NICU stay in neonates of hypothyroid women with thyroid antibodies [ 29 , 34 ]. Kiran et al have noted lower NICU admissions in women with thyroid antibodies [ 35 ]. Meena et al in 2016 have noted poor neonatal outcomes even in euthyroid women [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All hypothyroid pregnant females presenting to AKUH from 2008 till 2016 were included in this retrospective study. The in-depth methods and other details of the whole population characteristics can be reviewed in our previously published papers [ 9 , 20 ]. We reached a sample size of 280 hypothyroid pregnant women for this study objectives by applying the following eligibility criteria: Pregnant women of 18 years of age above, who had been diagnosed hypothyroidism, either overt (TSH > 10 mIU/mL and FT4 below normal range [10.30–23.17 pmol/L]) or subclinical (TSH > 10 mIU/mL and FT4 normal), by the clinician before pregnancy, as per chart review.…”
Section: Methodsmentioning
confidence: 99%
“…After further intensive reading of the articles, 6 articles without access to original data and uncontrolled studies were excluded. Finally, 13 studies were included for meta-analysis (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). The literature retrieval and screening process is illustrated in Figure 1.…”
Section: Literature Retrieval Processmentioning
confidence: 99%